Por um projeto urbano para Alcobaça: o vazio como oportunidade estratégica - Maria João Félix André (2020)
This dissertation is instigated by an urge to rethink some empty places, unoccupied or vacant spaces, in the city of Alcobaça. It is, therefore, motivated by a progressive interest in working on the city, with the objective of carrying out an intervention proposal that can promote its regeneration. Starting from an analysis of the urban morphology, of its evolution in relation to not only physical, of the territory, but also social constraints, it is through a careful reading of the current dynamics of the city that we move towards a reflection on urban voids. There are abandoned and vacant spaces in the consolidated fabric that can be seen as opportunities for revitalizing the historical area, which is becoming less and less inhabited. There are also in its surroundings expectant lands of considerable dimension, which can be decisive and enhancers of an intervention based on a logic of consolidation for the city. The empty places, although meaning absence, allow a certain freedom and expectation, proving to be essential to create poles that propel new spatial and social relations and, thus, trigger a process of urban revitalization. The purpose of this work is to demonstrate, through a project exercise, how the voids represent strategic opportunities for intervention, which can originate renewed urban spaces and integrate various functions that give them meaning, in response to wider needs of the city. The proposal is therefore positioned in an approach as an urban project, enhancing territorial effects beyond the area of intervention, through a global thought about the city and as recognition of its evolution in a continuous process over time.